The missing mitten mystery - Kellogg, Steven; Kellogg, Steven (New York : Dial Books for Young Readers, 2000)
Annie searches the neighborhood for her red mitten, the fifth she's lost this winter.
Re-worked edition of: The mystery of the missing red mitten. 1974.
AD 380
Keywords: Lost and found possessions -- Fiction; Mittens -- Fiction